Caracterização do processamento artesanal de produtos agropecuários em assentamentos rurais de Ilha Solteira-SP: das estratégias de produção à comercialização - Silva, Elisandra Alves [UNESP] (2015)
The family farmers encounter many difficulties of insertion in a livestock production model highly technified and competitive. To circumvent these challenges the grower quest different strategies to sustain the market, as the artisanal processing food products of agricultural origin. With the processing or others value adding procedures the grower obtains a differentiated product, by improving the income, and rescuing almost forgotten family traditions, due to the increasing industrialization, such as the preparation of sweets, cheeses, curd cheese, bread and other products, even though they are activities that are hindered by a series of legal demands. In this context, the present study aimed to conduct a study in the rural settlements Santa Maria da Lagoa and Estrela da Ilha, municipality of Ilha Solteira / SP, aiming to trace a general characterization of families and search properties, to know the strategies of value adding activity used by producers, the forms of processing, the installations and the main agricultural products used; verify the forms of marketing the products; investigate the the origin of the knowledge used to carry trough processing of the products; evaluate the economic importance, for the family, of these value adding processes; and verify possible differences in terms of gender relations related to the processing of products. The execution of research allowed to verify that the women's participation is the majority. For the benefited products by the farmers surveyed it found that dairy products are the most representative, with predominance of direct commercialization (at the producing establishment, in the consumer's residence and in street fair), the knowledge used in food processing, in the large majority of cases, is the of family origin (intergenerational), and only a few have sought technical improvement. The facilities for the manufacture of the product, in the almost all cases, it is the very ...